Revascularization vs. Medical Therapy in Stable Ischemic Heart Disease - Weiss, Sandra (Prog Cardiovasc Dis, 2015)
The keynote COURAGE and BARI-2D trials changed the way the interventional community selects patients for revascularization. What we now consider appropriate, especially for percutaneous coronary intervention, has narrowed significantly in scope compared to previous practice a decade ago. Medical therapy has been shown to be both safe and effective as a primary treatment modality for patients with stable ischemic heart disease on the whole. However, it appears that patients with a heavy ischemic burden may benefit from revascularization, although investigation of this is ongoing. Evidence preliminarily supports this practice with coronary artery bypass grafting, and possibly in specific populations undergoing multivessel intervention with functional assessment of lesion severity during PCI.